Coix seed oil ameliorates cancer cachexia by counteracting muscle loss and fat lipolysis - Huiquan Liu; Lu Li; Jun Zou; Ting Zhou; Bangyan Wang; Huihui Sun; Shiying Yu (BMC, 2019)
Abstract Background Cancer cachexia is a cancer-induced multifactorial debilitating syndrome directly accounting for 20% of cancer deaths without effective therapeutic approaches. It is extremely urgent to explore effective anti-cachexia drugs to ameliorate muscle and fat loss in cachexia patients. Methods Lewis lung carcinoma bearing C57BL/6 mice were applied as the animal model to examine the therapeutic effect of Coix seed oil (CSO) on cancer cachexia. The food intake and body weight change were monitored every 3 days throughout the experiment. The IL-6 and TNF-α levels in serum were detected by ELISA assay. Several key proteins involved in muscle wasting and fat lipolysis were tested by Western blot to identify the potential mechanism of CSO. Results Administration of CSO through gavage significantly prevented body weight loss and ameliorated systemic inflammation without affecting food intake and tumor size. The weight and histological morphology of gastrocnemius muscle and epididymal adipose tissue in CSO-treated mice were also improved. In mechanism, we found that CSO decreased the expression of MuRF1 and the ratio of phospho-p65 (Ser536) to p65 in muscle tissue. Meanwhile, cancer-induced activation of HSL and AMPK was also inhibited by CSO administration. Conclusion Coix seed oil exerts an anti-cachexia pharmaceutical effect by counteracting muscle and adipose tissue loss most likely through regulating NF-κB-MuRF1 and AMPK-HSL pathway.